EFEKTIVITAS HEALTH EDUCATION BERBASIS BOOKLET TERHADAP PERILAKU PENCEGAHAN GASTRITIS PADA REMAJA: EFFECTIVENESS OF BOOKLET-BASED HEALTH EDUCATION ON GASTRITIS PREVENTION BEHAVIOR IN ADOLESCENTS - Arreza, Aynur Auliya; Sudarso; Wijaya, Arif (LPPM STIKes Bahrul Ulum Jombang, 2025)
Gastritis is one of the common digestive disorders in adolescents, which is influenced by unhealthy lifestyles such as irregular eating habits, fast food consumption, lack of knowledge, and stress. This study aims to determine the effect of health education using booklet media on the level of gastritis prevention behavior in adolescents at MTS Thoriqul Huda Mojowarno Jombang. The research design used was pre-experimental with a one group pre-test and post-test approach. The research sample consisted of 69 respondents, this study used a probability technique with proportional random sampling. The instrument used was a questionnaire compiled based on indicators of gastritis prevention behavior. Data analysis was carried out using the Wilcoxon Signed Rank Test. Before the pre-test, the results showed that most 68.1% of respondents were categorized as sufficient, and after the post-test, the results showed that most 63.8% of respondents were categorized as good. The results showed a significant increase between the level of gastritis prevention behavior before and after being given health education through booklet media, with a p value of 0.000 <0.05. The conclusion of this study is that providing health education using booklet media is effective in improving gastritis prevention behavior in adolescents